Leadership in brazilian hospital nursing: contributions to the quality of patient care and safety (Research, Society and Development, 2020)
Objective: To identify in the scientific literature how the leadership of nurses contributes to the quality of care and patient safety in Brazilian hospitals. Method: Integrative literature review carried out from May to November 2019, in the Latin American and Caribbean Literature in Health Sciences databases, Scientific Electronic Library Online, Specialized Bibliographic Database in the Area of ​​Nursing, SCOPUS and Cumulative Index to Nursing and Allied Health Literature. In the synthesis of knowledge, a sample of 28 articles was analyzed. Results: Of the total sample, 21 (75%) articles came from field research, 4 (14%) were integrative reviews and 3 (11%) theoretical reflections. Studies prevailed in Rio Grande do Sul (39%), São Paulo (29%) and Santa Catarina (11%). Leadership proved to be a (in) direct way of contributing to the quality of care and patient safety in aspects related to assertive and participatory communication, healthier interpersonal relationships, inspiration from teams and people, technical competence, self-development, increased productivity, achievement of organizational goals, including assistance and more assertiveness in planning, giving rise to safe and sustainable care practices. Conclusion: In Brazilian hospitals, the nurse's leadership contributes to improving the quality of care and patient safety, especially due to the relational aspects that involve the production of care. However, there is room for other investigations that extract the direct influence of this competence in nursing on auditable elements of the work product.